Pro SQL Server 2008 Reporting Services - Landrum, Rodney (Springer, 2017)
Take full advantage of everything SQL Server 2008 Reporting Services has to offer and deliver customizable, web–enabled reports across your business at a reasonable cost. Learn best–practices from professionals who use SQL Server Reporting Services daily to deliver solutions to paying clients and gain the competitive edge on using Microsoft’s enterprise–level reporting platform.